The Impact Of Positive Reinforcement On The Self-Confidence Of Early Children In Grade A Of Anak Ceria Tembobor Kindergarten In The 2024/2025 Academic Year - Rina, Rina; Alawiyah, Tuti; Sukarto, Sukarto (JUPE : Jurnal Pendidikan Mandala, 2025)
Abstract..This study aims to explore how the application of self-confidence in Early Childhood Class A Kindergarten Ceria Children, in addition to exploring what factors affect the self-confidence of Early Childhood Class A Kindergarten Ceria Children and to analyze how the impact of giving positive reinforcement to Early Childhood Class A Kindergarten Ceria Children. The research method used is qualitative research with a case study approach.The results of the research at TK Anak Ceria, it can be concluded that the consistent application of positive reinforcement through verbal praise and nonverbal support has proven effective in increasing children's self-confidence, although internal (personality and family parenting) and external (less supportive school environment) factors also influence. The findings suggest that systematic interventions from educators are successful in creating a more supportive learning environment, although inconsistency in providing positive reinforcement remains a challenge. These results demonstrate the importance of a holistic approach in building children's self-confidence, and that reinforcing appropriate and sustained positive reinforcement has a significant impact on children's social-emotional development. Therefore, collaboration between teachers and parents in providing consistent and equitable support is key in optimizing early childhood confidence. Keywords: Positive Reinforcement, Early Childhood Self-Confidence